2020
DOI: 10.12788/3462
|View full text |Cite
|
Sign up to set email alerts
|

Should the Pendulum Swing Back? More Transfers to the ICU After Implementing Ward-Based High-Flow Nasal Cannula Initiation Protocols for Bronchiolitis

Abstract: As an appealing, physiologically plausible treatment, humidified oxygen delivery via high-flow nasal cannula (HFNC) has been rapidly adopted for the treatment of bronchiolitis despite weak evidence supporting its routine and early use in hypoxemic infants.1 Although HFNC use has been associated with decreased work of breathing and lower rates of progression to invasive ventilation in some studies, the one large trial published on the topic found no difference between early HFNC and standard oxygen therapy on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated reduced LOS, 11 decreased rate of ICU admission, 12 and reduced intubation rate. 8–10,13 Other studies have demonstrated no improvement in intubation rate or LOS 14,15 and instead showed an increased ICU admission rate 14,15 and higher resource utilization. 16 These data suggest that HFNC has become over-utilized in some patients who will not benefit from it, likely due to a lack of clear criteria for initiation of HFNC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated reduced LOS, 11 decreased rate of ICU admission, 12 and reduced intubation rate. 8–10,13 Other studies have demonstrated no improvement in intubation rate or LOS 14,15 and instead showed an increased ICU admission rate 14,15 and higher resource utilization. 16 These data suggest that HFNC has become over-utilized in some patients who will not benefit from it, likely due to a lack of clear criteria for initiation of HFNC.…”
Section: Introductionmentioning
confidence: 99%